2018
DOI: 10.1002/lipd.12084
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation Attenuates Chronic Hepatic Inflammation in High‐Fat Diet Fed Mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease worldwide. Hepatic inflammation is an important pathogenic mediator of NAFLD. There is currently no pharmacological agent approved for the treatment of NAFLD. Folic acid is a water‐soluble B vitamin that has been shown to have lipid‐lowering and antioxidant effects. The objective of this study was to investigate the effect of folic acid supplementation on hepatic inflammation and to identify the underlying mechanisms. Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
(64 reference statements)
0
14
0
3
Order By: Relevance
“…Previous studies have found that oral iron supplementation improved iron status, but also increased oxidative stress, even in women with low iron stores [24,25]. Interestingly, Tiwari et al [26] observed that although treatment with iron and folic acid has remarkable efficacy in terms of hemoglobin, it may also lead to impaired liver function in pregnant anemic women. It has recently been shown that folic acid ameliorates liver inflammatory processes [27] and hepatic steatosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that oral iron supplementation improved iron status, but also increased oxidative stress, even in women with low iron stores [24,25]. Interestingly, Tiwari et al [26] observed that although treatment with iron and folic acid has remarkable efficacy in terms of hemoglobin, it may also lead to impaired liver function in pregnant anemic women. It has recently been shown that folic acid ameliorates liver inflammatory processes [27] and hepatic steatosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic consumption of high-fat diets (HFD) is a major contributor to the development of obesity and metabolic abnormalities. In our previous studies, we observed an increased body weight gain and metabolic abnormalities (hyperlipidemia, hyperglycemia) in mice fed a HFD for 5-12 weeks (11)(12)(13)(14)(15)(16). Recent studies demonstrated renal injury in dietinduced obese mice, a murine model of CKD (7,17).…”
Section: Introductionmentioning
confidence: 93%
“…Asam folat juga dapat mengurangi tingkat sirkulasi mediator proinflamasi pada individu yang kelebihan berat badan dan pada pasien hiperhomosisteinemia (Solini et al, 2006;Wang et al, 2005). Pada penelitian pemberian asam folat oleh Sid et al (2018) pada tikus yang diberi makan HFD (High Fat Diet) yang dapat mengakibatkan fatty liver, mengungkapkan bahwa suplemen asam folat mengurangi peradangan hati pada tikus tersebut.…”
Section: Pembahasanunclassified
“…Kemampuan asam folat untuk menekan respons radang hati menunjukkan mikronutrien tersebut memiliki potensi terapi untuk manajemen fatty liver. Penelitian Sid et al (2018) menguatkan hasil pada pelitian ini bahwa pemberian asam folat mampu menekan stres oksidatif yang terjadi akibat pestisida karbamat, akan tetapi hasilnya tidak dapat mendekati kelompok normal walaupun telah berbeda signifikan jika dibandingkan dengan kelompok P1 induksi karbamat. Pemberian asam folat pada penelitian Sid et al (2018) diketahui selama 8 minggu atau selama minimal 56 hari, sementara dalam penelitian ini hanya dilakukan pemberian asam folat selama 14 hari.…”
Section: Pembahasanunclassified
See 1 more Smart Citation